2013
DOI: 10.1007/s00018-013-1286-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune suppression by neutrophils and granulocytic myeloid-derived suppressor cells: similarities and differences

Abstract: Neutrophils are essential effector cells in the host defense against invading pathogens. Recently, novel neutrophil functions have emerged in addition to their classical anti-microbial role. One of these functions is the suppression of T cell responses. In this respect, neutrophils share similarities with granulocytic myeloid-derived suppressor cells (G-MDSCs). In this review, we will discuss the similarities and differences between neutrophils and G-MDSCs. Various types of G-MDSCs have been described, ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
345
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(370 citation statements)
references
References 121 publications
14
345
0
11
Order By: Relevance
“…Neutrophils are known to polarize into protumoral phenotype in tumor-bearing hosts 16,17 and most of these immunosuppressive neutrophils are found in the spleen and tumors. 1,15 Consistent with these findings, we found that splenic and intratumoral neutrophils from control tumorbearing mice showed significant differences in surface marker expression compared with those from naive mice. Splenic neutrophils from control tumor-bearing mice showed the decreased expression of CD16 (Fcg receptor III), CD55 (Decay-accelerating factor), CD88 (C5a receptor), CD120a/b (TNF receptor), CD256 (TNF ligand superfamily member 13), CD137 (CD137, a TNF receptor family member), CD101 (immunoglobulin superfamily member 2), CD80 (co-stimulating molecule), and the increased expression of CD43 (leukosialin) and CD98 (large neutral amino acid transporter).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Neutrophils are known to polarize into protumoral phenotype in tumor-bearing hosts 16,17 and most of these immunosuppressive neutrophils are found in the spleen and tumors. 1,15 Consistent with these findings, we found that splenic and intratumoral neutrophils from control tumorbearing mice showed significant differences in surface marker expression compared with those from naive mice. Splenic neutrophils from control tumor-bearing mice showed the decreased expression of CD16 (Fcg receptor III), CD55 (Decay-accelerating factor), CD88 (C5a receptor), CD120a/b (TNF receptor), CD256 (TNF ligand superfamily member 13), CD137 (CD137, a TNF receptor family member), CD101 (immunoglobulin superfamily member 2), CD80 (co-stimulating molecule), and the increased expression of CD43 (leukosialin) and CD98 (large neutral amino acid transporter).…”
Section: Discussionsupporting
confidence: 81%
“…Neutrophils have been reported to gain more segments during differentiation; thus, hypersegmented neutrophils could represent "old" neutrophils. 15 Thus, we examined the effect of captopril on neutrophil survival. Neutrophils were exposed to 500 mM captopril for 12 h, and survival rates were determined using annexin V/propidium iodide (PI) staining.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, neutrophils regulate the recruitment and function of various cell types and interact with immune and nonimmune cells. Intriguingly, neutrophils directly affect Ag-specific responses by facilitating monocyte differentiation and dendritic cell maturation, and by interacting with T cells and B cells (4)(5)(6)(7)(8)(9)(10). Murine neutrophils have been shown to present Ags to both CD4 + and CD8 + T cells (11)(12)(13), and to differentiate into neutrophil-dendritic cell hybrids in vitro and in vivo (14,15).…”
mentioning
confidence: 99%